Acoustic tweezing cytometry enhances osteogenesis of human mesenchymal stem cells through cytoskeletal contractility and YAP activation. (July 2017) - Xue, Xufeng; Hong, Xiaowei; Li, Zida; Deng, Cheri X.; Fu, Jianping
Abstract: Human mesenchymal stem cells (hMSCs) have great potential for cell-based therapies for treating degenerative bone diseases. It is known that mechanical cues in the cell microenvironment play an important role in regulating osteogenic (bone) differentiation of hMSCs. However, mechanoregulation of lineage commitment of hMSCs in conventional two-dimensional (2D) monocultures or bioengineered three-dimensional (3D) tissue constructs remains suboptimal due to complex biomaterial design criteria for hMSC culture. In this study, we demonstrate the feasibility of a novel cell mechanics and mechanobiology tool, acoustic tweezing cytometry (ATC), for mechanical stimulation of hMSCs. ATC utilizes ultrasound (US) pulses to actuate functionalized lipid microbubbles (MBs) which are covalently attached to hMSCs via integrin binding to exert forces to the cells. ATC stimulation increases cytoskeletal contractility of hMSCs regardless of the cell area. Furthermore, ATC application rescues osteogenic differentiation of hMSCs in culture conditions that are intrinsically repressive for hMSC osteogenesis ( e.g., soft cell culture surfaces). ATC application activates transcriptional regulator YAP to enhance hMSC osteogenesis. Our data further show that F-actin, myosin II, and RhoA/ROCK signaling functions upstream of YAP activity in mediating ATC-stimulated hMSC osteogenesis. With the capability of applying controlled dynamic mechanical stimuli to cells, ATC provides a powerful tool for mechanoregulation of stem cell behaviors in tissue engineering and regenerative medicine applications.